Prokaryotic Production of Human Immunodeficiency VirusType 1 Subtype C Tat, Nef and Reverse Transcriptase andInvestigation of Antibody Responses to these proteins inHIV-1 Infected Individuals as well as Macaques Vaccinatedwith SAAVI DNA-C/C2 and SAAV - Kgatle, M M (Institute of Infectious Disease and Molecular Medicine, 2014)
The purified Tat, Nef and RT recombinant proteins were used as antigens to investigate the prevalence of HIV-1 antibodies in sera of HIV-1 infected people. There was no reactivity in any of the 20 negative control sera in the Western blot assay. Analysis of 481 sera from HIV-1 infected individuals showed that the majority of serum samples had relatively high prevalence of anti-RT antibodies, ranging from 89.9% to 95% irrespective of the clinical stages. Anti-Nef antibodies were observed in 47.4% of individuals tested and there was a strong association between the prevalence of these antibodies with the clinical stage of CD4 count range of 201 to 499 cells/μl. The prevalence of anti-Tat antibodies was less frequent and only 7.5% of serum samples had anti-Tat antibodies. There was no association of anti-Tat and anti-RT antibodies with viral load or CD4 counts in sera of HIV-1 infected individuals. Altogether, 92% of serum samples tested had positive antibody responses to one or more antigens, indicating a good performance for the Western blot detection method.The prevalence of antibody response against purified HIV-1 subtype C antigens (Tat, Nef and RT) was also investigated in eleven sera of macaques vaccinated with SAAVI DNA-C or SAAVI-DNA-C2 and SAAVI MVA-C. Western blot assays showed that 36%, 27% and 40% of serum samples from vaccinated rhesus macaques had detectable antibodies against HIV-1 subtype C Tat, Nef and RT antigens, respectively. The prevalence of antibody responses to Tat, Nef and RT antigens in the sera of macaques is lower relative to the prevalence of antibody responses in the sera of HIV-1 infected individuals. A possible explanation is that the immune system of HIV-1 infected people is continuously exposed to viral antigens, thus resulting to high level of detectable anti- Tat, -Nef and -RT antibodies. In contrast, macaques were exposed to HIV-1 antigens expressed by the DNA and MVA vectors for only five times through vaccinations. However, these results indicate that Western blot assay based on purified HIV-1 Tat, Nef and RT proteins may be a useful research tool for detection of antibody responses to corresponding vaccine immunogen in macaque sera.In conclusion, HIV-1 subtype C Tat, Nef and RT were successfully purified from Salmonella enterica serovar Typhimurium. The purified Tat, Nef and RT recombinant antigens were antigenically recognised by anti-Tat, anti-Nef and anti-RT antibodies in the sera of HIV-1 infected individuals and rhesus macaques vaccinated with candidate HIV-1 vaccines. Application of these purified proteins as reagents in a Western blot assay to detect antibodies in serum samples of HIV-1 subtype C positive individuals demonstrated an association between the prevalence of anti-Nef antibodies and CD4 count range of 201 to 499 cells/μl. In addition, the detection of antibody responses to purified Tat, Nef and RT antigens in the sera of vaccinated macaques suggests a possible application of these purified proteins in HIV vaccine research and improvement of existing Western blot-based HIV diagnostic kits.